RECENT ADVANCES IN THE APPLICATION OF HIGH DOSES OF ATORVASTATIN IN PATIENTS WITH CORONARY HEART DISEASE - M. V. Ezhov (Рациональная фармакотерапия в кардиологии, 2016)
The results of the recently completed clinical studies on the efficacy of atorvastatin in high doses are presented. In these studies high dose atorvastatin therapy was used in patients with acute coronary syndrome, chronic coronary heart disease, and percutaneous coronary interventions. Studies completed in Russia and devoted to efficacy of the high dose atorvastatin therapy are discussed specially.